A Possibilities for the Treatment of Diabetic Cardiac Autonomic Neuropathy - Victoria Serhiyenko; Marta Hotsko; Ludmila Serhiyenko; Alexandr Serhiyenko (Research Developments in Medicine and Medical Science Vol. 1, 2023)
This review aims to discuss the latest evidence regarding the current and future treatment of diabetic cardiac autonomic neuropathy (CAN). Search strategy. Scopus, Science Direct (from Elsevier), and PubMed including Medline databases were searched. In order to identify research results that could not be found during the online search, a manual search of the bibliography of publications was used. Lifestyle changes and intensive glycemic control may help to prevent the onset or progression of CAN. The pathogenetic management of CAN entails balanced hypocaloric diet and physical activity; optimization of glycemic control; treatment of dyslipoproteinemia; correction of metabolic abnormalities in myocardium; prevention and treatment of thrombosis; use of aldose reductase inhibitors; dihomo-Y-linolenic acid (DGLA), acetyl-L carnitine, antioxidants, first of all \(α\)-lipoic acid (\(α\)-LA), use of \(ω\)-3 and \(ω\)-6 polyunsaturated fatty acids (\(ω\)-3 and \(ω\)-6 PUFAs), vasodilators, fat-soluble vitamin B1, aminoguanidine; substitutive therapy of growth factors, in severe cases-treatment of orthostatic hypotension. Promising treatments include studying and using substances that improve blood flow through the vasa vasorum, such as prostacyclin analogues, thromboxane A2 blockers, and medications that help to strengthen and/or normalise Na+, K+-ATPase (phosphodiesterase inhibitor), \(α\)-LA, DGLA, (\(ω\)-3 PUFAs, and the simultaneous prescription of (\(α\)-LA), (\(ω\)-3 PUFA and DGLA.